Amputations in Sickle Cell Disease: Case Series and Literature Review. (3rd May 2016) - Maximo, Claudia; Olalla Saad, Sara T.; Thome, Eleonora; Queiroz, Ana Maria Mach; Lobo, Clarisse; Ballas, Samir K.
Abstract: In this study, we describe four new patients with sickle cell disease who had limb amputations. Two of the patients had sickle cell anemia [Hb S ( HBB : c.20A > T) (β S /β S )] with refractory leg ulcers that required amputations. The third patient had sickle cell trait with an extensive leg ulcer that was associated with epidermoid carcinoma. The fourth patient had amputations of both forearms and feet due to a misdiagnosis of dactylitis. Review of the literature showed that the indications for amputations in sickle cell disease included three distinct categories: mythical beliefs, therapeutic and malpractice. All therapeutic amputations were for severely painful, large, recalcitrant leg ulcers that failed non-interventional therapies. Amputation resulted in pain relief and better quality of life. Phantom neuropathic pain was not a major issue post-operatively. It was absent, transient or well controlled with antidepressants. Limb function was restored post-amputation with prosthetic artificial limbs, wheelchairs or crutches. Malpractice amputations were due to misdiagnosis or to cryotherapy by exposing the painful limb to ice water resulting in thrombosis, gangrene and amputation. We strongly suggest that leg amputations should be considered in the management of certain patients with severe extensive refractory leg ulcers, and topical cryotherapy should never be used to manage sickle cell pain.